Generation of particle assemblies mimicking enzymatic activity by processing of herbal food: the case of rhizoma polygonati and other natural ingredients in traditional Chinese medicine. Issue 8 (24th February 2021) - Benassi, Enrico; Fan, Haiyan; Sun, Qinglei; Dukenbayev, Kanat; Wang, Qian; Shaimoldina, Ainur; Tassanbiyeva, Aigerim; Nurtay, Lazzat; Nurkesh, Ayan; Kutzhanova, Aidana; Mu, Chenglin; Dautov, Adilet; et al.
Abstract : Processing of rhizoma polygonati-tai (huangjing-tai) or other herbs produces nanoparticle assemblies with enzyme activity, referred to as herbzymes. Abstract : Processed herbs have been widely used in eastern and western medicine; however, the mechanism of their medicinal effects has not yet been revealed. It is commonly believed that a central role is played by chemically active molecules produced by the herbs' metabolism. In this work, processed rhizoma polygonati (RP) and other herbal foods are shown to exhibit intrinsic phosphatase-like (PL) activity bounded with the formation of nano-size flower-shaped assembly. Via quantum mechanical calculations, an enzymatic mechanism is proposed. The enzymatic activity may be induced by the interaction between the sugar molecules distributed on the surface of the nanoassemblies and the phosphatase substrate via either a hydroxyl group or the deprotonated hydroxyl group. Meanwhile, the investigation was further extended by processing some fresh herbs and herbal food through a similar protocol, wherein other enzymatic activities (such as protease, and amylase) were observed. The PL activity exhibited by the processed natural herbs was found to be able to effectively inhibit cancer cell growth via phosphatase signaling, possibly by crosstalk with kinase signaling or DNA damage by either directly binding or unwinding of DNA, as evidenced by high-resolution atomic-force microscopy (HR-AFM). In this work, the neologism herbzyme (herb + enzyme) is proposed. This study represents the first case of scientific literature introducing this new term. Besides the well-known pharmacological properties of the natural molecules contained in herbs and herbal food, there exists an enzymatic/co-enzymatic activity attributed to the nanosized assemblies.